Influence of customized composite resin fibreglass posts on the mechanics of restored treated teeth - Anchieta, R. B. [UNESP]; Rocha, Eduardo Passos [UNESP]; Almeida, E. O. [UNESP]; Freitas Junior, A. C. [UNESP]; Martin Junior, M.; Martini, A. P. [UNESP]; Archangelo, C. M.; Ko, C. -C. (Wiley-Blackwell, 2012)
Aim To evaluate the mechanical behaviour of the dentine/cement/post interface of a maxillary central incisor using the finite element method and to compare the stresses exerted using conventional or customized post cementation techniques. Methodology Four models of a maxillary central incisor were created using fibreglass posts cemented with several techniques: FGP1, a 1-mm-diameter conventionally cemented post; CFGP1, a 1-mm-diameter customized composite resin post; FGP2, a 2-mm-diameter conventionally cemented post; CFGP2, a 2-mm-diameter customized composite resin post. A distributed load of 1N was applied to the lingual aspect of the tooth at 45 degrees to its long axis. Additionally, polymerization shrinkage of 1% was simulated for the resin cement. The surface of the periodontal ligament was fixed in the three axes (X =Y = Z = 0). The maximum principal stress (smax), minimum principal stress (smin), equivalent von Mises stress (svM) and shear stress (sshear) were calculated for the dentine/cement/post interface using finite element software. Results The peak of smax for the cement layer occurred first in CFGP1 (1.77 MPa), followed by CFGP2 (0.99), FGP2 (0.44) and FGP1 (0.2). The shrinkage stress (svM) of the cement layer occurred as follows: FGP1 (35 MPa), FGP2 (34), CFGP1 (30.7) and CFGP2 (30.1). Conclusions Under incisal loading, the cement layer of customized posts had higher stress concentrations. The conventional posts showed higher stress because of polymerization shrinkage.
Keywords: fibreglass post; finite element analysis; mechanics; resin-dentine interface; root canal